Cationic Arginine-Rich Peptides (CARPs): A Novel Class of Neuroprotective Agents With a Multimodal Mechanism of Action - Meloni, Bruno P.; Mastaglia, Frank L.; Knuckey, Neville W. (Frontiers in Neurology, 2020)
There are virtually no clinically available neuroprotective drugs for the treatment of acute and chronic neurological disorders, hence there is an urgent need for the development of new neuroprotective molecules. Cationic arginine-rich peptides (CARPs) are an expanding and relatively novel class of compounds, which possess intrinsic neuroprotective properties. Intriguingly, CARPs possess a combination of biological properties unprecedented for a neuroprotective agent including the ability to traverse cell membranes and enter the CNS, antagonise calcium influx, target mitochondria, stabilise proteins, inhibit proteolytic enzymes, induce pro-survival signaling, scavenge toxic molecules, and reduce oxidative stress as well as, having a range of anti-inflammatory, analgesic, anti-microbial and anti-cancer actions. CARPs have also been used as carrier molecules for the delivery of other putative neuroprotective agents across the blood-brain barrier and blood-spinal cord barrier. However, there is increasing evidence that the neuroprotective efficacy of many, if not all these other agents delivered using a cationic arginine-rich cell-penetrating peptide (CCPPs) carrier (e.g.,, TAT) may actually be mediated largely by the properties of the carrier molecule, with overall efficacy further enhanced according to the amino acid composition of the cargo peptide, in particular its arginine content. Therefore, in reviewing the neuroprotective mechanisms of action of CARPs we also consider studies using CCPPs fused to a putative neuroprotective peptide. We review the history of CARPs in neuroprotection and discuss in detail the intrinsic biological properties that may contribute to their cytoprotective effects and their usefulness as a broad-acting class of neuroprotective drugs.